Desenvolvimento de uma fonte de alimentação chaveada ajustável em tensão e corrente completamente controlada por microcontrolador e de alto fator de potência - Ventorini, Afonso (2007)
This work presents a 0-30 V / 0-5 A microcontroller-based switched-mode power supply, providing up to 150 W output. The proposed power supply has two stages. The input stage is a boost converter as a power factor pre-regulator, that provides universal input (127-220 V, 50/60 Hz) with power factor correction. The output stage is a two transistor forward converter, that allows voltage and current adjust. A single microcontroller is in charge of controlling the two converters, being responsible for keeping the dc bus voltage fixed (boost converter output) and adjusting the output voltage and current (forward converter output). The control loops were implemented using proportional-integral controllers. The converters are driven by pulse width modulation peripherals of the microcontroller, working at a constant frequency of 50 kHz. Furthermore, the microcontroller does the user interface task through potentiometers to select output voltage and current, and a liquid crystal display to show their values.